Pellagra. A case presentation. - Miguel González Muñoz; Oscar Liza Hernández; Vladimir Escobar Alfonso (Medisur)
The case of 39 years-old man with alcoholic antecedents is presented. Skin lesions, localized in characteristic areas, (hands and forehands dorsum, elbow joint, and neck) increased parallel to the intensity of the sunstroke. He had diarrhea and neurological disorders. In our case, lesion problems were solved including nicotinic acid, and a vitamin complex in his diet. Photoprotectives and emollients were also used. It is important to notice that pellagra is now associated to a new kind of patient: alcoholic persons and is no longer an exclusive marker of misery.